Identification and functional characterisation of a novel anther-specific LTP promoter from Brassica campestris ssp. chinensis. Issue 4 (3rd July 2016) - Tian, Aimei; Cao, Jiashu; Zhang, Enhui
ABSTRACT: The pollen development-related gene msLTP from Brassica campestris ssp. chinensis belongs to the lipid transfer protein (LTP) gene family. The promoter of the msLTP gene was isolated by thermal asymmetric interlaced PCR (TAIL-PCR). The functional elements of the promoter (named Bc15) were analysed. Some anther/pollen-specific elements, such as the GGTT box and the GTGA box, were identified in the sequence. In an attempt to confirm the promoter activity, a series of 5′-truncated constructs was fused with the GUS reporter gene to functionally analyse the key regulatory regions of the promoter. Transient expression analysis showed high GUS activity in onion epidermal cells containing the region from −731 to −1 bp. The truncated construct bearing the −731 to −1 bp fragment was stably introduced into Arabidopsis . Histochemical analysis of the transgenic plants showed distinct and specific GUS expression at different stages of anther/pollen development. Transverse sections of flower buds further indicated that the Bc15 promoter activates reporter gene expression in the anther specifically. These findings elucidated the molecular mechanisms of LTP gene regulation during pollen development, and suggested a potential application of the Bc15 promoter in engineering male sterility for hybrid production.